Middle Class Fortunes in Western Europe - Rakesh Kochhar (Luxembourg Income Study (LIS), 2017)
This paper examines the state of the middle classes in the U.S. and 11 countries in Western Europe and how it has changed since 1991. Among Western Europe's six largest economies, the shares of adults living in middle-income households increased in France, the Netherlands and the United Kingdom from 1991 to 2010, but shrank in Germany, Italy and Spain. France, the Netherlands and the UK also experienced notable growth in disposable household income, but incomes were either stagnant or falling in Germany, Italy and Spain. Ireland stands out as experiencing the most rapid growth in income from 1991 to 2010 and the biggest expansion of the middle class. Overall, the middle-class share fell in seven of the 11 Western European countries examined, mirroring the long-term shrinking of the middle class in the U.S. The decrease in the middle-class share is typically accompanied by a move up into the upper-income tier and a move down into the lower-income tier.
Keywords: 330; Income distribution; real income; inequality